LncRNA-mRNA Expression Profiles of Osteoclast After Conditional Knockout HIF-1α - Tian, Yuanye; Shao, Qi; Gu, Jiahong; Tang, Yi; Bie, Miaomiao; Zhou, Yangyifan; Cheng, Chunan; Liang, Yi; Zhang, Qian; Kang, Feiwu (Frontiers in Genetics, 2022)
Background: Osteoclasts, which are multinucleated cells formed by monocyte fusion, play a key role in bone resorption. Hypoxia-inducible factor (HIF)-1α is vital for the development of osteoclasts in hypoxic environments and during bone resorption. However, additional research is required to further study the HIF-1α-dependent regulation of osteoclast differentiation at the genetic level. Methods: In our study, RNA sequencing (RNA-seq) was used to identify the expression profiles of long noncoding RNAs (lncRNAs) and mRNAs in conditional HIF-1α-knockout osteoclasts. Results: A total of 1320 mRNAs and 95 lncRNAs were differentially expressed. The expression of lncRNAs MSTRG.7566.12 and MSTRG.31769.2 were strongly negatively correlated with that of Mmp9, Ctsk, etc. Conclusions: Our research provides a basis for further understanding the role of mRNAs and lncRNAs in conditional HIF-1α-knockout osteoclasts, and many of these molecules may be potential targets for treating bone diseases related to HIF-1α.